Polypharmacy, drug–drug interactions and adverse drug reactions in older Chinese cancer patients: evidence from CHARLS - Yan, Zijun; Fan, Ke-qin; Yu, Ting; Su, Ning; Zou, Yan; Xia, Liangjing (Frontiers in pharmacology, 2025)
To (i) quantify the prevalence of polypharmacy and clinically significant DDIs, (ii) examine their independent and combined associations with ADRs, and (iii) explore whether depression and cognition modify these relationships among older Chinese adults with cancer among older Chinese adults diagnosed with cancer. A total of 408 participants aged ≥60 years completed both the 2011 baseline and 2013 follow-up surveys, forming the analytic cohort. This analysis used data from the China Health and Retirement Longitudinal Study (CHARLS; 2011-2013). Eligible participants were community-dwelling adults aged ≥60 years who answered "yes" to the CHARLS question "Has a doctor ever told you that you had a malignant tumour or cancer?" (variable DAOO7-4, mapped to ICD-10 C00-C97). The most frequently reported sites were lung, stomach, colorectal, liver and breast cancers, yielding an analytic cohort of 408 individuals. Polypharmacy (≥5 medications/day) was determined through face-to-face interviews, and DDIs were identified using standardized reference compendia. ADRs were confirmed by self-reports corroborated with medical records. Depression and cognition were measured using validated scales. Logistic regression models adjusted for sociodemographic and clinical factors were used to evaluate associations. At baseline, 36.0% of participants reported polypharmacy, rising to 38.0% at follow-up. Clinically significant DDIs increased from 20.1% to 23.0%, while ADRs grew from 6.9% to 8.1%. In adjusted models, both polypharmacy (OR = 2.21, 95% CI = 1.14-4.30) and DDIs (OR = 3.28, 95% CI = 1.54-6.99) independently heightened ADR risk. Elevated depression scores were also linked to increased odds of ADRs, particularly among older women. Polypharmacy and DDIs substantially magnify the risk of ADRs in older Chinese adults with cancer, with depression further compounding vulnerability. Targeted medication management, careful DDI monitoring, and attention to psychosocial well-being may reduce preventable harms and improve outcomes in this rapidly expanding geriatric oncology population.